EFEKTIVITAS PEMBELAJARAN AL-QR’AN DALAM PENDIDIKAN ISLAM - Yazidul Bushtomi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
The Koran is the holy book for the Islamic religion throughout the world. As an eternal holy book, as well as guidance for all mankind. The Koran was revealed to the Prophet Muhammad through the angel Gabriel gradually, with the aim being that all humans could learn it gradually verse by verse. Effectiveness is a broad term that refers to a set of actions which, when measured in terms of quantity and quality and in accordance with previously planned programs, shows an increase in the level of success or achievement of a goal. Learning is the process of helping or guiding students as they learn. The effectiveness of learning the Koran is a set of actions in the form of a process of helping or guiding students when learning the Koran in accordance with a previously planned program, so that they can develop their potential in understanding the science of the Koran. The main assets for students in understanding Al-Qur'an learning are as follows: 1. Students have a high level of intelligence, 2. Students have motivation in learning, 3. Students are interested in learning, 4. Students are always healthy, 5 Students have good attitudes, 6. Students receive attention from their parents, 7. Teachers use appropriate methods for students.